New derivatives of sulfonylhydrazone as potential antitumor agents: Design, synthesis and cheminformatics evaluation - Sabbah Dima A.; Al-Azaideh Bara’a A.; Talib Wamidh H.; Hajjo Rima; Sweidan Kamal; Al-Zuheiri Aya M.; Sheikha Ghassan Abu; Shraim Sawsan (Acta Pharmaceutica, 2021)
Phosphoinositide 3-kinase α (PI3Kα) is a propitious target for designing anticancer drugs. A series of new N’-(diphenylmethylene)benzenesulfonohydrazide was synthesized and characterized using FT-IR, NMR (1H and 13C), HRMS, and elemental analysis. Target compounds exhibited an antiproliferative effect against the human colon carcinoma (HCT-116) cell line. Our cheminformatics analysis indicated that the para-tailored derivatives [p-NO2 (3) and p-CF3 (7)] have better ionization potentials based on calculated Moran autocorrelations and ionization potentials. Subsequent in vitro cell proliferation assays validated our cheminformatics results by providing experimental evidence that both derivatives 3 and 7 exhibited improved antiproliferative activities against HCT-116. Hence, our results emphasized the importance of electron-withdrawing groups and hydrogen bond-acceptors in the rational design of small-molecule chemical ligands targeting PI3Kα. These results agreed with the induced-fit docking against PI3Kα, highlighting the role of p-substituted aromatic rings in guiding the ligand-PI3Kα complex formation, by targeting a hydrophobic pocket in the ligand-binding site and forming π-stacking interactions with a nearby tryptophan residue.